Sustainable synthesis of L-phenylalanine derivatives in continuous flow by immobilized phenylalanine ammonia lyase - Roura Padrosa, David; Lehmann, Hansjoerg; Snajdrova, Radka; Paradisi, Francesca (Frontiers in Catalysis, 2023)
The application of phenylalanine ammonia lyases (PALs) for the amination of a variety of cinnamic acids has been shown to be a cost-efficient method to produce a variety of phenylalanine analogues. Nonetheless, as many other biocatalytic tools, the process intensification, especially due to the high equivalents of ammonia needed, and the cost-efficiency of the catalyst production and use have been key points to further prove their usefulness. Here, we investigated the use of previously characterized PALs (AvPAL and PbPAL) for the amination of a series of substituted cinnamic acids. To enhance the process scalability and the reusability of the catalyst, we investigated the use of covalent immobilization onto commercially available supports, creating a heterogeneous catalyst with good recovered activity (50%) and excellent stability. The immobilized enzyme was also incorporated in continuous flow for the synthesis of 3-methoxy-phenyl alanine and 4-nitro-phenylalanine, which allowed for shorter reaction times (20 mins of contact time) and excellent conversions (88 ± 4% and 89 ± 5%) respectively, which could be maintained over extended period of time, up to 24h. This work exemplifies the advantages that the combination of enzyme catalysis with flow technologies can have not only in the reaction kinetics, but also in the productivity, catalyst reusability and downstream processing.